Deformation monitoring of a steel structure using 3D terrestrial laser scanner (TLS) - Jatmiko, -; Psimoulis, Panos (2017)
Terrestrial Laser Scanner (TLS) offers a new approach of deformation analysis. Different from conventional equipment such as Global Navigation Satellite System (GNSS) and Total Station (TS), the entire surface of observed structure can be analysed by contactless measurement. However, until recently the application of laser-scanner is still limited to long-term deformation monitoring . Using TLS to monitor dynamic response faces some challenges, such as scan time delay and its data characteristic. This project proposed helical mode to solve these issues and tested the proposed solution in a high-rise artwork deformation monitoring case, the Aspire Sculpture in Nottingham. The result showed that scan time delay can be solved. Then TLS can be used to observe the sculpture dynamic deformation. New approach of point cloud processing was introduced in order to extract the deformation. Using this approach, laser-scanner can be used to monitor dynamic motion of a structure.